Development of Risky Decision Making: Fuzzy‐Trace Theory and Neurobiological Perspectives. (10th April 2015) - Reyna, Valerie F.; Wilhelms, Evan A.; McCormick, Michael J.; Weldon, Rebecca B.
Abstract Developmental differences in mental representations of choices, reward sensitivity, and behavioral inhibition (self‐control) explain greater susceptibility to risk taking. Ironically, relying on precise representations in reasoning promotes greater risk taking, but this reliance declines as adolescents mature. This phenomenon is known as a developmental reversal; it is called a reversal because it violates traditional developmental expectations of greater cognitive complexity with maturation. Fuzzy‐trace theory (FTT) predicts reversals by proposing two types of mental representation (gist and verbatim), and that risk takers rely more on verbatim processing when making decisions. In this article, we describe the main tenets of FTT and explain how it can account for risky decision making. We also explore the neural underpinnings of development and decision making in the context of distinctions from FTT. FTT's predictions elucidate unanswered questions about risk taking, providing directions for research.